2021
DOI: 10.1002/ece3.7783
|View full text |Cite
|
Sign up to set email alerts
|

No effect of passive integrated transponder tagging method on survival or body condition in a northern population of Black‐capped Chickadees (Poecile atricapillus)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Incident rate of leg injuries that were potentially related to tagging in our study population were below 0.005%. Furthermore, a study on small passerine birds found no differences in survival or body condition of tagged versus untagged individuals (Farr et al, 2021), indicative of no negative long‐term effects of tagging. The use of puzzle boxes in combination with RFID technology therefore not only provides a low‐cost method for conducting socio‐cognitive experiments on wild animals in their natural environment, but is also of low ethical concern.…”
Section: Discussionmentioning
confidence: 99%
“…Incident rate of leg injuries that were potentially related to tagging in our study population were below 0.005%. Furthermore, a study on small passerine birds found no differences in survival or body condition of tagged versus untagged individuals (Farr et al, 2021), indicative of no negative long‐term effects of tagging. The use of puzzle boxes in combination with RFID technology therefore not only provides a low‐cost method for conducting socio‐cognitive experiments on wild animals in their natural environment, but is also of low ethical concern.…”
Section: Discussionmentioning
confidence: 99%
“…tarsus, bill length, bill depth, wing length), body mass was recorded, and a small blood sample was collected from the brachial vein to allow for molecular sexing [21]. As part of another study aimed at assessing the effects of passive integrated transponder (PIT) tags and methods on chickadees, from 2017 to 2019, birds were randomly assigned to receive no PIT tag, a PIT tag attached a colour band, or a PIT tag implanted subcutaneously [22]. Because we relied on radio frequency identification (RFID) to detect birds at feeders (see below), the data presented here are only for chickadees that were fitted with leg band PIT tags, as the implanted PIT tags were found to have unreliable detectability (see [2] for further details).…”
Section: Methodsmentioning
confidence: 99%
“…Before releasing each bird, we fitted a passive integrated transponder (PIT) tag (2.12x10mm;CYNTAG, Inc;Item#: 601205-2248) to the tarsometatarsus of each adult following the methods established in Bridge and Bonter (2011) to monitor parental visitation. The PIT tags are small coils of magnetic wire programed with a unique 10digit code that can be read by any radio frequency identification (RFID) system (Bridge and Bonter, 2011;Bridge et al, 2019;Farr et al, 2021). We gave every bird a unique combination of color bands and multicolored heat shrink tubing incasing the PIT tags (Figure 1A) to allow us to visually identify individuals using binoculars.…”
Section: Subjectsmentioning
confidence: 99%